IMPACT OF WORKLOAD AND MOTIVATION ON EMPLOYEE PERFORMANCE - Adira Ineswari; Sahang Sapta Apritchzeki; Harjoko Harjoko (POLITEKNIK LP3I JAKARTA, 2026)
This study aimed to analyze whether Workload and Work Motivation simultaneously have a significant effect on Employee Performance in the Production Division of PT Pusan Manis Mulia. This research employed a quantitative approach using primary data collected through questionnaires, observations, and interviews with employees at PT Pusan Manis Mulia. The population consisted of 200 employees from the Production Division of PT Pusan Manis Mulia registered through the e-catalog system in 2025. The sample consisted of 67 respondents. The sampling technique utilized non-probability sampling with a saturated sampling method. Variable measurement was conducted using a Likert scale. The analytical method employed was multiple linear regression analysis processed using SPSS version 24.